2018
DOI: 10.1126/science.aao5360
|View full text |Cite
|
Sign up to set email alerts
|

Coherent, atomically thin transition-metal dichalcogenide superlattices with engineered strain

Abstract: Epitaxy forms the basis of modern electronics and optoelectronics. We report coherent atomically thin superlattices in which different transition metal dichalcogenide monolayers-despite large lattice mismatches-are repeated and laterally integrated without dislocations within the monolayer plane. Grown by an omnidirectional epitaxy, these superlattices display fully matched lattice constants across heterointerfaces while maintaining an isotropic lattice structure and triangular symmetry. This strong epitaxial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
348
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 291 publications
(361 citation statements)
references
References 64 publications
10
348
1
2
Order By: Relevance
“…Recently, many studies have been reported on the strain effect of 2D layered materials [10][11][12]. This effect has been proved that the optical band gap can be tuned by up to several hundred meV/% in atomically thin TMDs by local strain [13].…”
Section: Introductionmentioning
confidence: 98%
“…Recently, many studies have been reported on the strain effect of 2D layered materials [10][11][12]. This effect has been proved that the optical band gap can be tuned by up to several hundred meV/% in atomically thin TMDs by local strain [13].…”
Section: Introductionmentioning
confidence: 98%
“…The heterostructures of 2D materials with graphene also induce the change of graphene's shape and the configuration of the heterostructures, giving rise to novel electronic and photoelectric properties 2,33,34. More importantly, the electronic and optical performances of 2D semiconductors can be further tuned by strain engineering for device applications 35,36…”
Section: Introductionmentioning
confidence: 99%
“…This progress is clearly reflected in the description of HSs systems, which has changed from alloys to interfaces. Recent experiments have shown remarkable control on sharpness [37] and strain at the interface [36,38]. Moreover, atomically sharp interfaces between crystalline phases of the same TMD, 1T'-WSe 2 and 1H-WSe 2 , have been studied in the search for topologically protected helical edge states [39].…”
Section: Introductionmentioning
confidence: 99%